2022
DOI: 10.3855/jidc.16166
|View full text |Cite
|
Sign up to set email alerts
|

Severe pneumonia caused by Chlamydia psittaci: report of two cases and literature review

Abstract: Introduction: Chlamydia psittaci pneumonia is a zoonotic infectious disease caused by Chlamydia psittaci. Its clinical manifestations are nonspecific. Diagnosis of the disease is difficult. In recent years, next-generation sequencing has played an important role in pathogen detection. We report two cases with severe Chlamydia psittaci pneumonia confirmed by next-generation sequencing. Case Study: The first case is that of a 50-year old man who presented with high fever for four days and cough with sputum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
4
0
1
Order By: Relevance
“…Previous study had shown that people infected with C. psittaci often presented with influenza‐like atypical symptoms, such as fever, chills, headache, myalgia and fatigue, with or without respiratory symptoms 14 . The disease could progress to severe pneumonia, and most cases were curable with few dead cases 15–18 . Analogously, all patients in our study showed fever, with the peak value median of 39.55°C (range 38.7–40.5°C).…”
Section: Discussionsupporting
confidence: 70%
“…Previous study had shown that people infected with C. psittaci often presented with influenza‐like atypical symptoms, such as fever, chills, headache, myalgia and fatigue, with or without respiratory symptoms 14 . The disease could progress to severe pneumonia, and most cases were curable with few dead cases 15–18 . Analogously, all patients in our study showed fever, with the peak value median of 39.55°C (range 38.7–40.5°C).…”
Section: Discussionsupporting
confidence: 70%
“…The previous literature mainly includes individual cases, and lacks a summary of large samples. For example, Dai et al published 2 cases of CPP (7). Zhao et al reported a comparative study of 6 CPP cases with 31 COVID-19 cases (8).…”
Section: Introductionmentioning
confidence: 99%
“…According to certain research, psittacosis patients had normal white blood cell counts and high neutrophil percentages, as well as possible abnormalities in the liver and kidneys, electrolyte changes, elevated CRP, and decreased ALT [11] , [12] , [18] . Our patient presented to us with an increased white blood cell count, which might have been caused by different bacterial illnesses.…”
Section: Discussionmentioning
confidence: 99%